2003
DOI: 10.1091/mbc.e03-01-0046
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mode for Integrin-mediated Signaling: Tethering Is Required for Phosphorylation of FAK Y397

Abstract: The common model for integrin mediated signaling is based on integrin clustering and the potential for that clustering to recruit signaling molecules including FAK and src. The clustering model for transmembrane signaling originated with the analysis of the EGF receptor signaling and remains the predominant model. The roles for substrate-bound ligand and ligand occupancy in integrin-mediated signaling are less clear. A kinetic model was established using HT1080 cells in which there was a linear relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
113
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 45 publications
7
113
0
Order By: Relevance
“…In contrast, the Col I-induced FAK activation is tension-independent because the ligand GFOGER motif in Col I is readily accessible to integrin α2. Therefore, our data showed that integrin α subunits play crucial roles in determining the mechanosensitivity of FAK activation, as the adhesion of HT1080 cells to FN or Col I is dependent on integrin α5β1 (15,28) or α2β1 (29-31), respectively (SI Appendix, Fig. S2 and Fig.…”
Section: Distinct Biophysical Mechanism Of Fak Mechanoactivation Detementioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, the Col I-induced FAK activation is tension-independent because the ligand GFOGER motif in Col I is readily accessible to integrin α2. Therefore, our data showed that integrin α subunits play crucial roles in determining the mechanosensitivity of FAK activation, as the adhesion of HT1080 cells to FN or Col I is dependent on integrin α5β1 (15,28) or α2β1 (29-31), respectively (SI Appendix, Fig. S2 and Fig.…”
Section: Distinct Biophysical Mechanism Of Fak Mechanoactivation Detementioning
confidence: 83%
“…Therefore, the ligation of α subunit and the ECM proteins converges at the integrin β1 activation and shares the mechanism of FAK activation. The clustering of integrin β1 by activating antibody AG89 was previously shown to induce the FAK phosphorylation on Tyr861, but not Tyr397, in the suspended HT1080 cells (28). 12G10 recognizes the βA domain of integrin β1 at the ligand-binding region (33), whereas AG89 recognizes the membrane proximal stalk-like regions of integrin β1 (34).…”
Section: Distinct Biophysical Mechanism Of Fak Mechanoactivation Detementioning
confidence: 97%
“…MYO1E SH3-mediated autoinhibition of MYO1E motor function (26) may be released by MYO1E binding to FAK. MYO1E binding to FAK then tethers FAK to actin, which may promote endocytosis (18) and could explain why FAK function is tightly linked to actomyosin dynamics and integrin endocytosis (10,27). Upon FAK Y397 autophosphorylation, SRC binds FAK through SH2 domain interaction, which, in turn, releases SRC SH3 to interact with FAK PRR1, thereby possibly replacing MYO1E.…”
Section: Discussionmentioning
confidence: 99%
“…Y397 is nonphosphorylated (9). Upon activation by tethering (10) or other stimuli that induce conformational change (11), the linker region is exposed and Y397 becomes autophosphorylated, leading to the recruitment of the protooncogene SRC. FAK and SRC then form a transient complex, which stabilizes FAK in its active conformation and induces changes in cell shape and focal adhesion turnover in vitro (12).…”
mentioning
confidence: 99%
“…It has been previously shown that the strength of HT1080 cell adhesion to either FN coatings or fibrillar FN matrices is drastically decreased upon antibody blocking of α 5 β 1 -integrin [37,38]. In contrast, blocking of α v β 3 -integrin does not significantly affect fibrosarcoma cell adhesion [38,39], although this integrin type binds to fibrillar FN [40] and is important for adhesion to FN in other cell lines. Upon α 5 β 1 -integrin blocking, the reduced migration speed on FN coatings suggests that cell binding via α 5 β 1 -integrin is necessary for promoting migration in 2D.…”
Section: α 5 β 1 -Integrin Binding To Fibronectin Modulates Tumor Celmentioning
confidence: 98%